Microscopic assessment of the tissue‐sparing potential of radiofrequency‐assisted liver resection techniques in a porcine model. (14th November 2017) - Ypsilantis, Petros; Lambropoulou, Maria; Milicevic, Miroslav; Bulajic, Predrag; Karayiannakis, Anastasios; Zacharoulis, Dimitrios; Simopoulos, Constantinos
Abstract: Background: The aim of the present study was to microscopically assess the tissue‐sparing potential of contemporary radiofrequency‐assisted liver resection (RF‐LR) techniques. Methods: Twenty‐four pigs were subjected to either (1) partial hepatectomy (PH) using the sequential‐coagulate‐cut (SCC) technique (group SCC, n = 6) using a monopolar electrode, the technique using the bipolar electrode Habib‐4X (group H, n = 6) or the "crush‐clamp" technique (group CC, n = 6); or (2) sham operation (group Sham, n = 6). At 48 h post‐operation, liver parenchyma proximal to the ablation rim was excised for histopathologic examination and immunohistochemical assessment of apoptosis (antibody M30) and inflammatory response (antibodies IL‐6, TNFα and NFκB). Results: Histopathologic index increased from the 1 st to the 4 th, the 1 st to the 2 nd or only the 1 st cm from the inner margin of the ablation rim in group SCC, H or CC, respectively. The index was higher in group SCC compared to the other groups. Tissue expression of M30, IL‐6, TNFα and NFκB increased in all PH groups, being higher and more expanded in group SCC, H, SCC and SCC, respectively. Conclusions: RF‐LR techniques had variable microscopically assessed tissue‐sparing effect. The Habib‐4X proved to be less injurious compared to the SCC Belgrade technique regarding the severity and extent of tissue damage proximal to the ablation rim. Abstract : Highlight Ypsilantis and colleagues assessed the tissue‐sparing potential of contemporary radiofrequency‐assisted liver resection techniques in a porcine model. Resection with the Habib 4X bipolar resection device was less injurious than that with the sequential coagulation‐cut technique in terms of the severity and extent of tissue damage proximal to the ablation rim.